Design of JD155 Permanent Magnet Synchronous Traction Motor for Metro Vehicle - FU Minli; HE Siyuan; LI Yifeng; PENG jun (Kongzhi Yu Xinxi Jishu)
This paper describes the design method based on multi-physics coupling simulation of permanent magnet synchronous traction motor for rail transit. Taking JD155 permanent magnet synchronous traction motor for Shenyang Metro Line 2 as an example, it introduces the selection of critical parameters, structure, testing and operation of the motor and the comparison with asynchronous traction motor. The next stage of work is then proposed. The experiments show that the JD155 permanent magnet synchronous traction motor has more advantages than asynchronous traction motor in the aspects of efficiency and energy-saving, maintenance, outline dimension etc.